2018
DOI: 10.1016/j.socscimed.2018.07.028
|View full text |Cite
|
Sign up to set email alerts
|

Leveraging smallholder livestock production to reduce anemia: A qualitative study of three agroecological zones in Ghana

Abstract: Livestock production and Animal-Source Foods (ASFs) like meat, milk, and eggs are excellent sources of essential micronutrients, including iron and zinc. There is evidence that encouraging increased access to and consumption of these ASFs may either positively or negatively impact anemia, or have no nutritional effects. Drawing upon first-hand experiences in Ghana, this study sought to: (1) identify the main motivations for raising livestock in Ghana; (2) describe the major barriers to consuming ASFs, especial… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

5
13
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 18 publications
(18 citation statements)
references
References 36 publications
5
13
0
Order By: Relevance
“…Furthermore, the present study witnessed that priorities were given for fathers for certain ASFs such as chicken and meat, and avoidance for children below two years was reported although not all participants agreed on this view point. Similar research findings were reported in Ghana by Nyantakyi-Frimpong et al [30] and Colecraft et al [33] who stated that some ASFs are more favored to fathers and old people compared to the other families in the community. The perception of our study participants about the avoidance of meat to children is also supported by Colecraft et al [33] and Nakachew et al [55].…”
Section: Discussionsupporting
confidence: 87%
See 4 more Smart Citations
“…Furthermore, the present study witnessed that priorities were given for fathers for certain ASFs such as chicken and meat, and avoidance for children below two years was reported although not all participants agreed on this view point. Similar research findings were reported in Ghana by Nyantakyi-Frimpong et al [30] and Colecraft et al [33] who stated that some ASFs are more favored to fathers and old people compared to the other families in the community. The perception of our study participants about the avoidance of meat to children is also supported by Colecraft et al [33] and Nakachew et al [55].…”
Section: Discussionsupporting
confidence: 87%
“…The presence of livestock in-kind credit program was reported to be opportunities to facilitate the consumption of ASFs among children in the study area. In line with this finding, livestock in-kind credit was stated as a possible intervention for the barriers that decline the consumption of ASFs among women of reproductive age in Ghana [30]. The finding aligns with a study done in Rwanda [68] and Ethiopia [69] which has shown that these interventions truly increase ASF consumption and improve nutritional status.…”
Section: Discussionsupporting
confidence: 76%
See 3 more Smart Citations